The impact of digitalization on enterprise value creation: An empirical analysis of Chinese manufacturing enterprises - Fanlin Meng; Wenping Wang (Journal of Innovation & Knowledge (JIK), 2023)
This study proposes a novel production function of digital empowerment. It constructs a theoretical framework to analyze the digital enabling process for enterprises from the production factor and economic activity aspects. It uses data mining technology to measure the degree of digitalization, extracts a typical relationship model between digitalization degree and enterprise performance, and digs out the association rules among traditional factors, digital factors, and economic activities under different relationship models. The results show that the digitalization degree and the digitalization enabling the level of mechanical and electronic enterprises are higher than those of light textile enterprises and resource-processing enterprises. The substitution elasticities and the association rules among factors and activities also have enterprise heterogeneity, which leads to differences in the digital transformation paths of different types of enterprises.
Keywords: 650; Association rules; Data mining technology; Digital empowerment production function; Enterprise performance; Substitution elasticity